2019
DOI: 10.3389/fchem.2019.00569
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Performance of ZnSe Electrospinning Nanofibers as an Anode Material for Lithium Ion and Sodium Ion Batteries

Abstract: ZnSe nitrogen-doped carbon composite nanofibers (ZnSe@N-CNFs) were derived as anode materials from selenization of electrospinning nanofibers. Electron microscopy shows that ZnSe nanoparticles are distributed in electrospinning nanofibers after selenization. Electrochemistry tests were carried out and the results show the one-dimensional carbon composite nanofibers reveal a great structural stability and electrochemistry performance by the enhanced synergistic effect with ZnSe. Even at a current density of 2 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 48 publications
(61 reference statements)
0
31
0
Order By: Relevance
“…The authors reported that NiS 2 nanoparticles/carbon nanofiber as SIBs anode display a high-performance with a good specific capacity of 500 mAh g −1 at 0.1 A g −1 and also a competitive rate with storage of 200 mAh g −1 at 2 A g −1 , in addition to long-lasting consistency within 1000 cycles. Besides, Zhou et al studied the performance of the ZnSe electrospinning nanofiber form PAN in lithium and sodium batteries as anode materials [136]. They showed that ZnSe@N-CNFs present an excellent performance in LIBs and also in SIBs at higher current density.…”
Section: Electrochemical Batteriesmentioning
confidence: 99%
“…The authors reported that NiS 2 nanoparticles/carbon nanofiber as SIBs anode display a high-performance with a good specific capacity of 500 mAh g −1 at 0.1 A g −1 and also a competitive rate with storage of 200 mAh g −1 at 2 A g −1 , in addition to long-lasting consistency within 1000 cycles. Besides, Zhou et al studied the performance of the ZnSe electrospinning nanofiber form PAN in lithium and sodium batteries as anode materials [136]. They showed that ZnSe@N-CNFs present an excellent performance in LIBs and also in SIBs at higher current density.…”
Section: Electrochemical Batteriesmentioning
confidence: 99%
“…For the sake of overcoming these problems, one of effective strategy is to design ZnSe/C nanocomposite, which can availably buffer strain of volume variation in the lithiation/ delithiation process and provide adequate diffusion paths of lithium ions. [10][11][12][13][14] For example, Ji et al designed carbon-coated hollow ZnSe sphere by Ostwald ripening method and the ZnSe/ C sphere retained a reversible capacity (574 mAh g À 1 at 1 A g À 1 ). [10] Feng et al demonstrated ZIF-8 derived ZnSe polyhedra/RGO composites could maintain stable capacity of 464 mAh g À 1 at 2 A g À 1 .…”
Section: Introductionmentioning
confidence: 99%
“…[11] It is also confirmed that ZnSe/C electrospinning nanofiber displayed improved electrochemical properties. [12] Based on the above mentioned electrochemical properties of ZnSe/C nanocomposites, it is observed that constitution, morphology, and pore structure for the ZnSe/C nanocomposites can synergistically affect the cyclability of the ZnSe/C anode. Therefore, to further improve electrochemical property of ZnSe/C anode materials for LIBs, it deserves to continue exploring novel ZnSe/C nanocomposites by facile strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Rechargeable lithium-ion batteries, an environmentally friendly and new green energy, have wide applicability in the fields of energy storage and transportation (Song et al, 2018). The ever-increasing demand for high current charge-discharge capability, high energy density, and long service life has driven the development of the lithium battery industry (Zhou et al, 2019). Olivine phase lithium iron phosphate (LiFePO 4 ) is one of the focused cathode materials in lithiumion batteries (Padhi et al, 1997a,b).…”
Section: Introductionmentioning
confidence: 99%